The association between expressed emotion, illness severity and subjective burden of care in relatives of patients with schizophrenia. Findings from an Italian population - Carrà Giuseppe; Cazzullo Carlo Lorenzo; Clerici Massimo (BMC Psychiatry, 2012)
Abstract Background An appropriate understanding of the association between high-Expressed Emotion (EE) in family members of people with schizophrenia, patients’ and relatives’ correlates is needed to improve adaptation of psychoeducational interventions in diverse cultures. The aim of this study was to test the hypothesis that relatives designated as high EE would report higher subjective burden of care, and would be associated with objective variables that indicate greater illness severity i.e. number of previous hospitalizations and duration of illness. Methods We performed secondary analyses of baseline data from a randomized controlled trial conducted in Italy. Results High-EE relatives reported more subjective burden of care in disturbed behaviours and adverse effects areas, but did not perceive more deficits in social role performances. As regards illness severity characteristics, neither the number of previous hospital admissions nor the duration of illness was associated with high-EE. However, patients’ previous psychosocial functioning, as measured by educational attainments, seems to protect the relative from high-EE status. Conclusion There is a need for cross-cultural comparisons of the subjective experience of distress and burden among high EE carers as a target for intervention, aimed at reducing family stress as much as improving patient outcomes.